ANALISIS STRUKTUR NAVIGASI ANTARAMUKA PENGGUNA PADA PENYEBARAN INFORMASI PUBLIK BERBASIS WEB (STUDI KASUS WEBSITE DEPARTEMEN NEGARA RI) - Mgs Afriyan Firdaus (Universitas Sriwijaya, 2009)
According to the user's perspective, User interface is visible and important part of the computer system; that require the highest priority in the design of computer systems (Jaspers, 2006). There are many aspects to web design. According to Vandelay (2007), successful website is made by content quality, simple and interactive design, easy to navigate, unique, fresh, and optimize. Design context will be the great importance related to the dissemination of public information. According to Act No. 14/2008 on the Openness of Public Information that Each of Public Information is open and can be accessed by any user of Public Information and Each of Public Information should be obtained by each Public Information’s applicant quickly and on time, low cost and with less effort. Information dissemination efforts through the web are often hampered by the difficulty of navigation in a website. This study examined the structure of navigation in the website’s user interface of any departments within the Republic of Indonesia to find out how difficult public information can be accessed through the website. The method is carried out in this study is the observation, literature study and analysis of 20 website’s user interface in the environment department of the Republic of Indonesia. The results obtained from this study is that the user can easily access public information, because all the website’s homepage displays the latest news or information and almost all websites have a search section to find out necessary information in the website. And the user will not be confused in knowing their positions, because in most cases the department has implemented a web site using a signpost and window title page, logo web pages, tabs and indicator selection. In addition, users can learn about the flow to get public information with the use of wayfinding, that is good signage, environmental clues and maps.Key words: public information, user interface, websites, departments, navigation